Automated Controlled Underwater Rover using Raspberry Pi - et. al., Dr P Ashok Babu , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper proposes to design and develop and automated controller underwater rover by the usage of raspberry pi. A underwater remotely controlled vehicle is named as a submerged rover as it is distantly controlled by the highest point of the host transport over the water surface. Presently the operational rule of a submerged meanderer isn't like a distantly controlled vehicle or robot. Along these lines, a steel link is of extraordinary need for a legitimate association among the client at the host transport and the submerged wanderer as this is a distantly controlled meanderer. There lies an incredible assortment of its relevance; it tends to be utilized for receiving the live video or still photos of the submerged life and all the submerged exercises to find out regarding the submerged life. It construct the work for jumpers, rescuer and pearl gatherers simpler as the wanderer provides the photos, live video and the wide range of various significant subtleties vital for having legitimate information about the submerged components. The submerged wanderer motor can be fabricated utilizing numerous sorts yet here we will examine about Raspberry Pi controlled motor submerged meanderer; i.e; a ROV submerged meanderer utilizing Raspberry Pi. Here we are proposed a method called monitor a parameter in rover the parameters like temperature, humidity, co2, pressure to store the data into the cloud we don’t have a good internet at the rover (submarines) so we are using lora transmitter send data to the network area first and receive the data at lora receiver and sent notifications if there any abnormal parameters in rover.